NetSuite ERP for Administrators : Learn How to Install, Maintain, and Secure a NetSuite Implementation, Using the Best Tools and Techniques. - Bickof, Anthony (Packt Publishing Ltd, 2018)
NetSuite ERP is a complete, scalable cloud ERP solution targeted at fast-growing, mid-sized businesses and large enterprises. It's the smartly executed combination of financial management operations and built-in business intelligence, which enables companies to make data-driven and well-informed decisions. This book will help administrators ...